Decomposing the Effects of CCTs on Entrepreneurship - Lichand, Guilherme (World Bank, Washington, DC, 2012)
This note assesses whether Bolsa-Familia increases the probability of starting a venture in Brazil by decomposing its potential effects into three channels: wealth-constraint alleviation, insurance provision, and reduction of children's labor supply (through the effect of the conditionality). Results are that entrepreneurship is indeed stimulated by Bolsa-Familia in urban areas through the insurance and wealth-constraint alleviation effects, notwithstanding that new ventures are typically secondary sources of income. The conditionality seems not to impact the level of entrepreneurship. Hence, Bolsa-Familia might have a positive long-term effect as well, instead of just offering short-term poverty relief.